A short time-step point rainfall stochastic model - Thauvin, V.; Gaume, E.; Roux, C. (Water Science and Technology, 1998)
This paper deals with the development of a point rainfall stochastic model, which generates synthetic sequences of 5 min rainfall rates. This time step is necessary to derive correctly the short hydrological response of urban catchments. The model simulates dry and rainy sequences in alternance. Particular attention has been paid to intense periods which are of utmost importance as far as flooding is concerned. This leads us to describe a rain event as a juxtaposition of inter-showers and showers. The intensity of an inter-shower is assumed to remain constant. Showers are defined as a succession of << peaks >> with a single maximum and a trapezoidal shape. The model has been calibrated with raingauge data from the Seine Saint Denis area, situated near Paris, in France. This paper presents the definition of the model variables, the calibration of their probability distributions and the initial validation results. The conclusion insists on the fact that for the model to be completed, hydrological validation is necessary. (C) 1998 Published by Elsevier Science Ltd. All rights reserved.